Adult attention deficit hyperactivity disorder and violence in the population of England: does comorbidity matter? - Rafael A González; Constantinos Kallis; Constantinos Kallis; Jeremy W Coid (PLoS ONE)
Background It is unclear whether the association between Attention Deficit/Hyperactivity Disorder (ADHD) and violence is explained by ADHD symptoms or co-existing psychopathology. We investigated associations of ADHD and its symptom domains of hyperactivity and inattention, among individuals reporting violence in the UK population. Methods We report data from the Adult Psychiatric Morbidity Survey (2007), a representative sample of the household population of England. A randomly selected sample of 7,369 completed the Adult Self-Report Scale for ADHD and the self-reported violence module, including repetition, injury, minor violence, victims and location of incidents. All models were weighted to account for non-response and carefully adjusted for demography and clinical predictors of violence: antisocial personality, substance misuse and anxiety disorders. Results ADHD was moderately associated with violence after adjustments (OR 1.75, p = .01). Hyperactivity, but not inattention was associated with several indicators of violence in the domestic context (OR 1.16, p = .03). Mild and moderate ADHD symptoms were significantly associated with violence repetition, but not severe ADHD where the association was explained by co-existing disorders. Stratified analyses further indicated that most violence reports are associated with co-occurring psychopathology. Conclusions The direct effect of ADHD on violence is only moderate at the population level, driven by hyperactivity, and involving intimate partners and close persons. Because violence associated with severe ADHD is explained by co-existing psychopathology, interventions should primarily target co-existing disorders.